Anthropocene islands: There are only islands after the end of the world. Issue 3 (November 2021) - Chandler, David; Pugh, Jonathan
Many Anthropocene scholars provide us with the key take home message that they are writing 'after the end of the world'. Not because they are writing about apocalypse, but because they are engaging the Anthropocene after the profound crisis of faith in Western modernity which has swept across academia in recent decades. Here the dominant problematic of contemporary Anthropocene thinking has rapidly turned away from modernity's human/nature divide to that of 'relational entanglements'. Thus, Anthropocene scholarship is taking a particular interest in geographical forms and cultures which are held to bring this problematic to the fore for more intensive interrogation. In this article, we examine how the figure of the island as a liminal and transgressive space has facilitated Anthropocene thinking, working with and upon island forms and imaginations to develop alternatives to hegemonic, modern, 'mainland', or 'one world' thinking. Thus, whilst islands, under modern frameworks of reasoning, were reductively understood as isolated, backward, dependent, vulnerable, and in need of saving by others, the island is being productively re-thought in and for more recent Anthropocene thinking. We explain how islands have shifted from the margins in a number of international debates, becoming key sites for understanding relational entanglements, enabling alternative forms of thought and practice in the Anthropocene.